Stimulus-Induced Seizures in Sick Neonates - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
Researchers at New York-Presbyterian Hospital, Cornell Medical College, NY, describe 3 (11.5%) sick neonates with stimulus-induced seizure occurring during continuous video-EEG monitoring of a cohort of 26 neonates July-Dec 2007.